John Tracy Ellis : an American Catholic reformer - Shelley, Thomas J. (The Catholic University of America Press, 2023)
"For several decades prior to his death in October1992, Monsignor John Tracy Ellis was the most prominent historian of American Catholicism. His bibliography lists 395 published works, including seventeen books, most famously, American Catholics and the Intellectual Life, a scathing indictment of the mediocrity of Catholic higher education and a clarion call for American Catholics to make a greater contribution to American intellectual life. Ellis's ecumenically-minded scholarship led to his election in 1969 as the President of both the American Catholic Historical Association and the predominantly Protestant American Society of Church History. As a professor at the Catholic University of America, Ellis trained numerous graduate students, who made their own contributions to American Catholic history, and he also furthered the careers of several talented young church historians. Especially in his later years, during the polarized atmosphere that followed Vatican II, Ellis became an outspoken but balanced advocate of reform in the Church, urging greater transparency and honesty, collegiality on the diocesan level, a role for the laity in the selection of bishops, reassessment of church teaching on birth control, decentralization to provide an enhanced role for the local churches, and an eloquent defense of religious freedom and the American Catholic commitment to separation of church and state. His fellow church historian, Jay P. Dolan, remarked that Ellis "used history as an instrument to promote changes he believed necessary for American Catholicism....No other historian of American Catholicism matched Ellis in this regard.""--